2021
DOI: 10.14203/j.mev.2021.v12.51-56
|View full text |Cite
|
Sign up to set email alerts
|

Bi-fluid cooling effect on electrical characteristics of flexible photovoltaic panel

Abstract: A photovoltaic (PV) system integrated with a bi-fluid cooling mechanism, which is known as photovoltaic thermal (PVT) system, was investigated. The electrical characteristics of flexible solar panel were evaluated for PV and PV with bi-fluid (air and water) cooling system. The integration of monocrystalline flexible solar panel into both systems was tested under a fixed solar radiation of 800 W/m2. A total of 0.04–0.10 kg/s of air flow was utilised in PV with cooling system with a fixed water mass flow rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Ben Hamida and Hatami (2021) examined the effect of fins in a channel, considering various hybrid nanofluids, on the thermalhydraulic performance under an electrical field. Dezfouli et al, 2017;HameedJaaz et al, 2017;Hasan et al, 2017;Jaaz et al, 2017;Hasan et al, 2018b;Hasan et al, 2018c;Ben Hamida and Hatami, 2021;Rukman et al, 2021;Abdulrasool et al, 2022;Hasan et al, 2022a;Ameen et al, 2022;Hasan et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ben Hamida and Hatami (2021) examined the effect of fins in a channel, considering various hybrid nanofluids, on the thermalhydraulic performance under an electrical field. Dezfouli et al, 2017;HameedJaaz et al, 2017;Hasan et al, 2017;Jaaz et al, 2017;Hasan et al, 2018b;Hasan et al, 2018c;Ben Hamida and Hatami, 2021;Rukman et al, 2021;Abdulrasool et al, 2022;Hasan et al, 2022a;Ameen et al, 2022;Hasan et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…The numerical results revealed that the rectangular ribs could improve the thermal performance by approximately 47.7% when compared to the plain absorber tube. A relatively large number of studies, including experimental, theoretical, and simulation, have been conducted to reveal the effects of various techniques that can improve the heat transfer enhancement potential in numerous applications such as heat exchangers, solar air heaters, solar thermal systems, solar cooling systems, solar flat-plate collectors, and solar evacuated tube collectors ( Al-Shamani et al, 2016 ; Naje et al, 2016 ; Al-Waeli et al, 2017 ; Dezfouli et al, 2017 ; HameedJaaz et al, 2017 ; Hasan et al, 2017 ; Jaaz et al, 2017 ; Hasan et al, 2018b ; Hasan et al, 2018c ; Ben Hamida and Hatami, 2021 ; Rukman et al, 2021 ; Abdulrasool et al, 2022 ; Hasan et al, 2022a ; Ameen et al, 2022 ; Hasan et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed an important thermal enhancement due to applying the water jet-impingement to PV-cell cooling. Many other studies were carried out to present the impact of heat-transfer enhancement on the performance of different solar systems in different engineering application [23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Also it was found it the coil diameter reduced from 0.3m to 0.04m, the capillary tube length is reduced by about 10% which improves of the performance of the system.The demand of minimizing the high cost and energy resulted in many efforts to enhance the performance of cooling systems [6] . The techniques of heat transfer enhancement have been classified into two categories such as passive and active techniques [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . The massive increase in population across the world has caused a very high demand on resources including water, electricity, and housing.…”
Section: Introductionmentioning
confidence: 99%